الحماية القانونية للمعطيات ذات الطابع الشخصي على ضوء القانون رقم 18-07 دراسة تحليلية - يحي, تومي (Université de M'sila, 2020)
ملخص تنصب دراستنا حول الحماية القانونية للأشخاص الطبيعيين في مجال معالجة المعطيات ذات الطابع الشخصي من خلال أحكام نصوص القانون رقم 18-07 المؤرخ في 10 يونيو 2018، ونظرا للاستعمال الواسع لتكنولوجيا الاعلام والاتصال الحديثة في شتى مجالات الحياة خاصة في مجال المعالجة الالية للبيانات ، وفي ظل العولمة وسهولة الحصول على البيانات وتداولها، تتضاعف أهمية ارساء نظام فاعل للحماية ، وفرض اجراءات قانونية صارمة تحمي الأشخاص الطبيعيين في مجال معالجة المعطيات ذات الطابع الشخصي ،الأمر الذي دفع المشرع الجزائري إلى اعتماد اطار قانوني وتنظيمي ملائم لحماية المعطيات الشخصية يسمح بتحديد أوجه الحماية للفرد ولمعطياته الشخصية بدءا بتكريس المبادئ الأساسية لحماية المعطيات الشخصية، والاجراءات الخاصة بعملية المعالجة الألية للمعطيات واحترام حقوق الأشخاص المعنيين بالمعالجة(كالحق في الاعلام والحق في الولوج والحق في التصحيح والحق في الاعتراض) تضمن لهم سلامة معطياتهم الشخصية وفق ألية مؤسساتية تتمثل في انشاء السلطة الوطنية لحماية المعطيات الشخصية المنصوص عليها في القانون رقم 18-07 و جزاءات جنائية تردع المخالفين لقواعد معالجة المعطيات ذات الطابع الشخصي ، وهو ما تعرضنا له بالتحليل والمناقشة في دراستنا لهذا الموضوع .من خلال عرضنا للنظام القانوني والأليات القانونية لحماية المعطيات الشخصية. Abstract Our study focuses on the legal protection of natural persons in the treatment of personal data through the provisions of Law No. 18-07 of June 10, 2018, and due to the wide use of modern information and communication technology in various areas of life, especially in the field of automated data processing, and in the context of globalization. The importance of establishing an effective system of protection, and the imposition of strict legal procedures to protect natural persons in the processing of personal data, makes the Algerian legislator adopt an appropriate legal and regulatory framework for the protection of private data. A mandate that allows the protection of the individual and his / her personal data, starting with the establishment of basic principles for the protection of personal data, procedures for the automatic processing of data and respect for the rights of the persons concerned with the treatment (such as the right to information, the right to access, the right to rectification and the right to object) to ensure the integrity of their personal data according to an institutional mechanism In the establishment of the National Authority for the Protection of Personal Data provided for in Law No. 18-07 and criminal penalties deter violators of the rules of processing data of a personal nature, which we have been analyzed and discussed in our study of this subject. The legal system offered legal mechanisms and aa personal data protection
Keywords: الكلمات المفتاحية : حماية المعطيات الشخصية، المعالجة وشروطها ، الحماية الجزائية . ; Keywords: Protection of personal data, processing and conditions, penal protection